Analysis on the factors related to the acute success rate of fluoroless catheter ablation in patients with supraventricular tachycardias: a single-center experience. (25th November 2020) - Jan, M; Yazici, M; Habjan, S; Prolic Kalinsek, T; Topalovic, M; Zizek, D; Stublar, J; Rupar, K; Lakic, N
Abstract: Background: In this retrospective study, we aimed to detect factors related to the acute success rate (ASR) of radiofrequency (RFA) and cryo-ablation (CRA) of SVTs guided by three-dimensional (3D) electroanatomical mapping (EAM) system completely without the use of fluoroscopy (FLR). Methods and results: We analyzed 324 consecutive patients with SVTs [age was 30.65±20.71 (3.6–83.1) years, 147 patients <19 years old and 50.3% (163/224) patients were female]. There were 112 patients with accessory pathways (APs), 36 patients with atrial tachycardia (ATs), and 176 patients with atrioventricular nodal reentrant tachycardia (AVNRT). All procedures [(RFA (n=257), CRA (n=51), combined RFA and CRA (n=16)] were performed guided by the 3D EAM system completely without the use of FLR. Intracardiac echocardiography (ICE) was used as an imaging tool when transseptal approach was needed for treatment of left-sided arrhythmias. The acute success rate (ASR) was 90.4% (293/224). There were no procedural complications. After the first procedure, patients were divided into the "ablation success" group (group I, n=293) and the "ablation failure" group (group II, n=31). Two groups were similar in terms of age, BMI, gender distribution, and type of ablation procedure. In group II, number of ablation lesions was significantly higher than group I [respectively; 17.93±11.7 vs. 10.5±14.5; p=0.003]. Additionally, total ablation time (TAT) [respectively; 552.6±298.6 vs. 449.7±448.1; p=0.1] and total procedural time (TPT) [respectively; 116.3±54.2 vs. 94.5±82.0; p=0.05] were mildly higher. When compared to Group I, the number of patients with right-sided tachycardias was significantly higher in Group II.[67.74% (21/31 vs. 21.5% (63/293; p<0.001]. ASR was the highest for patients with AVNRT and lowest for patients with ATs [respectively; 95.4% (168/176) vs. 75.0% (27/36); p<0.001]. Binary logistic regression analysis (Nagelkerke R Square=0.201) showed that SVTs originating from the right side were an independent risk factor for procedural failure. Patients with right-sided SVTs faced an approximately 11-fold increased risk of failed ablation (OR=10.69, 95% CI 2.49–45.78, p=0.001). Type of arrhythmia, type of ablation procedure, the sex category, age, and BMI were not independent risk factors for failed ablation. A significant risk factor for recurrence could not be detected. Conclusions: This study revealed that catheter ablation of SVTs completely without the use of fluoroscopy can be performed with high ASR and without procedural complications. Likewise, ASR of fluoroless ablation was the highest for patients with AVNRT and lowest for patients with AT. Moreover, right-sided SVTs were an independent risk factor for ablation failure. Funding Acknowledgement: Type of funding source: None